Technology-Aided Programs to Support Positive Verbal and Physical Engagement in Persons with Moderate or Severe Alzheimer’s Disease - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; D’Amico, Fiora; Renna, Caterina; Pinto, Katia (Frontiers in Aging Neuroscience, 2016)
Pilot studies using technology-aided programs to promote verbal reminiscence and mild physical activity (i.e., positive forms of engagement) in persons with moderate or severe Alzheimer’s disease have provided promising results (Lancioni et al., 2015a,b). The present two studies were aimed at upgrading and/or extending the assessment of those programs. Specifically, Study 1 upgraded the program for verbal reminiscence and assessed it with eight new participants. The upgraded version automatically monitored the participants’ verbal behavior during the sessions, in which photos and brief videos were used to foster verbal reminiscence. Monitoring allowed computer approval and reminders to be consistent with the participants’ behavior. Study 2 extended the assessment of the program for promoting mild physical activity with 10 new participants for whom arm-raising responses were targeted. The results of Study 1 showed that the participants’ mean percentages of intervals with verbal engagement/reminiscence were below 10 during baseline and control sessions and between above 50 and nearly 80 during the intervention. The results of Study 2 showed that the mean frequencies of arm-raising responses were about or below four and between about 10 and 19 per session during the baseline and the intervention, respectively. The general implications of the aforementioned results and the need for new research in the area were discussed.